Matilda - Dahl, Roald; Blake, Quentin (New York, N.Y., U.S.A. Puffin Books, 1990)
Matilda applies her untapped mental powers to rid the school of the evil, child-hating headmistress, Miss Trunchbull, and restore her nice teacher, Miss Honey, to financial security.
Keywords: Schools -- Fiction; Humorous stories